Practical Nihilism - Elijah Millgram (Philosophies, 2022)
Nihilism about practical reasoning is the thesis that there is no such thing as practical rationality—as rationally figuring out what to do. While other philosophers have defended a theoretically oriented version of the thesis, usually called “error theory”, a case is made for a fully practical version of it: that we are so bad at figuring out what to do that we do not really know what doing it right would so much as look like. In particular, much of our control of instrumental (or means-end) rationality is illusory, and we are almost entirely incompetent at managing the defeating conditions of our practical inferences—that is, of knowing when not to draw an apparently acceptable conclusion. If that is right, then instead of trying to reason more successfully, we should be trying to make failure pay.